Fibroblastic reticular cell tumor of eyelid: Rare case report and review of literature - Pragnya P. Mishra; K Madan; Siddhartha Biswas; Anuradha Calicut Kini Rao (Indian Journal of Pathology and Microbiology)
Fibroblastic reticular cell tumours (FRCT) originate from the fibroblastic reticular cells (FBRC) which are histiocytic cells, belonging to the dendritic cell family. These tumours are extremely rare, with only a few cases reported in literature. Histomorphologically, they resemble follicular dendritic cell sarcoma (FDCS); however, they differ immunophenotypically. Extranodal presentations are rare. We report a case of malignant FBRC tumour of the left eyelid, in a 23-year-old woman, who had presented with a recurrent swelling over left lower eyelid. Microscopy revealed an ill circumbscribed tumour composed of oval to spindle cells in storiform pattern, sprinkled with lymphocytes. Immunohistochemistry was performed and diagnosis of FRCT was offered. To the best of our knowledge, this is the first report of malignant FBRC tumour arising in the eyelid region. Here we present this extremely rare case with review of the available literature.